Assessing the Efficacy of Plant Extracts in Managing Postharvest Fungi (Alternaria alternata and Penicillium expansum) on Apple Fruits - Abdulsayid Mohammed; Abdulkhalig Moftah; Abdlmanam Fakron (AlQalam Journal of Medical and Applied Sciences, 2025)
The efficacy of wormwood, thyme, and camphor extracts on fungal growth and spore formation was evaluated using potato dextrose agar (PDA) medium, with each extract dissolved separately in water, alcohol, and hexane. The study results showed that aqueous and alcoholic camphor extracts most significantly inhibited fungal growth, with reductions to 0.87 cm for Penicillium. expansum and 0.8 cm and 1.08 cm, respectively, for Alternaria. alternata. Hexane and aqueous thyme extracts were most effective in preventing P. expansum spore formation, at 1.49% and 1.97%, respectively, while hexane wormwood extract most inhibited A. alternata spore formation at 1.46%. These extracts were also tested for their efficacy in controlling apple fruit rot induced by P. expansum and A. alternata under storage conditions in Red Delicious and Golden Delicious cultivars. Notably, the aqueous wormwood extracts limited P. expansum infection in Red Delicious apples to 7%. The study revealed that certain plant extracts effectively prevented fungal infection in apple fruits. Specifically, no infection was detected in fruits treated with alcoholic and hexane wormwood extracts, alcoholic thyme, or hexane camphor. Among Golden Delicious apples, the hexane camphor extract treatment resulted in the lowest P. expansum infection rate (3.5%), whereas the aqueous wormwood extract treatment led to the highest infection rate (65%). In Red Delicious apples, the highest A. alternata infection rate (2.1%) was observed with alcoholic thyme extract treatment. Conversely, no infection was observed in fruits treated with wormwood (alcoholic and hexane), aqueous thyme, or alcoholic and hexane camphor extracts. Additionally, Golden Delicious apples treated with alcoholic wormwood extract exhibited complete resistance to A. alternata infection.